Study on non-saponification extraction process for rare earth separation - 肖燕飞 龙志奇 黄小卫 冯宗玉 崔大立 王良士 (Journal of rare earths, 2013)
The purpose of this study was to overcome the disadvantages of ammonia-nitrogen wastewater pollution and high cost of sodium saponification in rare earth separation process. The study focused on the non-saponification extraction technology with magnesia. The influences of the content and particle size of magnesia, reaction time, reaction temperature, and O/A on cerium extraction rate were also discussed. The results showed that the hydrogen ions of extractant were exchanged by rare earth ions when organic ex- tractant and rare earth solution were mixed with magnesia powder, and then the exchanged hydrogen dissolved magnesia to make the acidity of the system stable. The magnesium ions were not participated in the extraction reaction. Non-saponification extraction process of rare earth had been realized. The cerium extraction rate could reach up to 99% in single stage within the optimal reaction conditions.